2021
DOI: 10.1136/bmjhci-2021-100458
|View full text |Cite
|
Sign up to set email alerts
|

Association of persistent acute kidney injury and renal recovery with mortality in hospitalised patients

Abstract: ObjectivesAcute kidney injury (AKI) affects up to one-quarter of hospitalised patients and 60% of patients in the intensive care unit (ICU). We aim to understand the baseline characteristics of patients who will develop distinct AKI trajectories, determine the impact of persistent AKI and renal non-recovery on clinical outcomes, resource use, and assess the relative importance of AKI severity, duration and recovery on survival.MethodsIn this retrospective, longitudinal cohort study, 156 699 patients admitted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 27 publications
1
18
0
1
Order By: Relevance
“…To include also lower stage AKI is relevant. Hoste et al found an odds ratio above two for mortality relative to non‐AKI in the KDIGO group 1 patients, 5 and similar results have been shown also by others as well as in our study 18,19 . Whether these relationships indicate that AKI is a cause for increased mortality or that there is a shared cause for both AKI and increased mortality is unknown.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…To include also lower stage AKI is relevant. Hoste et al found an odds ratio above two for mortality relative to non‐AKI in the KDIGO group 1 patients, 5 and similar results have been shown also by others as well as in our study 18,19 . Whether these relationships indicate that AKI is a cause for increased mortality or that there is a shared cause for both AKI and increased mortality is unknown.…”
Section: Discussionsupporting
confidence: 86%
“…Hoste et al found an odds ratio above two for mortality relative to non-AKI in the KDIGO group 1 patients, 5 and similar results have been shown also by others as well as in our study. 18,19 Regarding risk factors for developing AKI, we observed a correlation between a lower blood pressure expressed by TAMAP and the development of AKI, and a correlation between the hypotensive dose, described as TWA-MAP<73, and the incidence of AKI, showing significantly more AKI in those having a higher dose of hypotension. Our results are comparable to a UK study, which found that a perfusion pressure of less than 60 mmHg was associated with a progression of AKI.…”
Section: Discussionmentioning
confidence: 73%
“…Bhatraju et al found that recovering within the first 72 h immediately following the AKI episode may be crucial to avoid major adverse kidney events [44]. Compared to a rapid reversal (within 48 h), persistent AKI was also significantly associated with a higher 1-year mortality rate [45]. Recovery timing therefore appears to be a major factor in the context of AKI recovery, which adds important prognostic information regarding adverse long-term outcomes following an AKI episode.…”
Section: Discussionmentioning
confidence: 99%
“…For data collection, a structured questionnaire prepared by the researcher and based on scientific evidence [ 6 , 17 , 18 ] was used, consisting of 16 questions, with the following variables: gender, age, ethnicity, weight, Body Mass Index, hospitalization time in the medical clinic, comorbidities, renal replacement therapy during the medical clinic stay, and laboratory variables (serum creatinine and urea) extracted from the patient’s electronic medical chart.…”
Section: Methodsmentioning
confidence: 99%
“…In the intensive care setting, the mortality detected at one year was five times higher among patients with AKI without recovery, when compared to those with a history of rapidly reversed AKI [ 6 ] and, in non-critical care, mortality after 12 months affected 64.9% of the patients who presented with AKI [ 6 ]. A cohort study indicates that, of 534 non-critical patients with AKI, 45% presented full renal recovery and that, among them, 9% died still while hospitalized [ 1 ].…”
Section: Introductionmentioning
confidence: 99%